2014
DOI: 10.1001/jama.2014.303
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in Older Women

Abstract: IMPORTANCE Asymptomatic bacteriuria and symptomatic urinary tract infections (UTIs) in older women are commonly encountered in outpatient practice. OBJECTIVE To review management of asymptomatic bacteriuria and symptomatic UTI and review prevention of recurrent UTIs in older community-dwelling women. EVIDENCE REVIEW A search of Ovid (Medline, PsycINFO, Embase) for English-language human studies conducted among adults aged 65 years and older and published in peer-reviewed journals from 1946 to November 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
180
5
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(198 citation statements)
references
References 76 publications
5
180
5
8
Order By: Relevance
“…However, this study demonstrates that more concern should be directed toward diabetic patients with previous APN. Diabetes increases the risk of UTIs (17,18) and their recurrence (19), which might place diabetic patients at risk of acquiring ESBL-EC as a result of repeated antibiotic exposure (1,(20)(21)(22). In this study, we found that the risk of acquiring ESBL-EC was markedly increased in diabetic patients with a history of APN, whereas either factor alone was not an independent risk factor.…”
Section: Discussionmentioning
confidence: 52%
“…However, this study demonstrates that more concern should be directed toward diabetic patients with previous APN. Diabetes increases the risk of UTIs (17,18) and their recurrence (19), which might place diabetic patients at risk of acquiring ESBL-EC as a result of repeated antibiotic exposure (1,(20)(21)(22). In this study, we found that the risk of acquiring ESBL-EC was markedly increased in diabetic patients with a history of APN, whereas either factor alone was not an independent risk factor.…”
Section: Discussionmentioning
confidence: 52%
“…Although cost-benefit analyses and clinical practice guidelines discourage treatment of asymptomatic bacteriuria in older adults, this practice frequently occurs in ambulatory care (15). Once a diagnosis is established, antibiotic selection for UTIs among older outpatients should be based on previous uropathogen susceptibility profiles, when available, and be weighed carefully against potential adverse drug events, comorbidities, and medication interactions (15).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, dysuria is identified reliably. The presence of dysuria appears to be one of the strongest predictors of bacteriuria plus pyuria in nursing home residents, and new dysuria is the most helpful clinical finding in identifying UTI in older adults [5253]. …”
Section: Defining Clinical and Laboratory Criteria For Utimentioning
confidence: 99%